FAKTOR-FAKTOR YANG MEMENGARUHI KEPUASAN PELANGGAN LISTRIK PRABAYAR PADA PT. PLN (PERSERO) UNIT INDUK UP3 PAREPARE - Wahyuddin, Hilmawati (Economos : Jurnal Ekonomi dan Bisnis, 2019)
This study discusses understanding service, quality, price, and emotional factors on customer satisfaction. The data collection techniques used in this study are Observation, Interview, Questionnaire and Documentation. The research sample is payment of 100 customers who use prepaid electricity. Data analysis techniques in this study used multiple linear analysis techniques. Based on the results of research that has been done carried out on the results of the analysis that is estimated Based on the results of the analysis obtained factors that increase customer satisfaction with service Y. However, service, quality, price, emotional factors that simultaneously affect customer satisfaction (Y).